Protein requirement in juveniles of the marine fish Chita Anisotremus scapularis (Tschudi, 1846) (Perciformes: Haemulidae) - Yanac P., Ciro (2023)
The present study was carried out to determine the protein requirement in Peruvian grunt juvenile, Anisotremus scapularis. In total, 72 fish weighing 19.95 ± 4.09 g and length of 10.31 ± 0.63 cm were used. They were randomly distributed in groups of six units per tank. The experimental diets contained protein levels of 45, 50, 55 and 58%, which were supplied to three experimental units per diet. The fish were fed three times a day to satiety for a period of 56 days. The results showed that final weight, weight gain, feed intake and feed conversion ratio were significantly (p<0.05) affected by dietary protein levels. However, the increase in size and the specific growth rate did not present significant differences (p>0.05) between treatments. The protein requirement based on weight gain using second degree polynomial regression was 56.78%, for optimal growth of Peruvian grunt juveniles.